2011
DOI: 10.1074/jbc.m111.274993
|View full text |Cite
|
Sign up to set email alerts
|

A Three-part Signal Governs Differential Processing of Gli1 and Gli3 Proteins by the Proteasome

Abstract: Background: Three Gli transcription factors mediate Hedgehog signaling. The proteasome remodels two Glis by degrading them only partially. Results: The extent of degradation is affected by three elements in Gli3: a folded structure, a linker, and a correctly spaced degron. Gli1 lacks two of them. Conclusion: A three-component signal determines whether Gli proteins are remodeled. Significance: These findings elucidate an unusual post-translational regulatory mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…3H). Taken together with the previous results, we conclude that the natural partial processing of DnaX requires both a tightly folded domain and a glycine-rich region, similar to those requirements for the 26S proteasome (28,29). We note that because DnaXnp is degraded slowly, it is possible that partial fragments of DnaXnp are transiently generated but are degraded so rapidly relative to full-length protein that they are undetectable by our methods.…”
Section: Partial Processing Of Dnax Requires Folded Domains Adjacent Tosupporting
confidence: 85%
See 1 more Smart Citation
“…3H). Taken together with the previous results, we conclude that the natural partial processing of DnaX requires both a tightly folded domain and a glycine-rich region, similar to those requirements for the 26S proteasome (28,29). We note that because DnaXnp is degraded slowly, it is possible that partial fragments of DnaXnp are transiently generated but are degraded so rapidly relative to full-length protein that they are undetectable by our methods.…”
Section: Partial Processing Of Dnax Requires Folded Domains Adjacent Tosupporting
confidence: 85%
“…3A). Interestingly, the 26S proteasome is known to stall at glycine-rich regions during ubiquitin-mediated proteolysis if those regions are adjacent to tightly folded domains (28,29), and more recently, a similar effect has been shown with engineered substrates of ClpXP in vitro (30). We addressed if processing of DnaX followed similar rules by generating a construct containing residues 317-608 that removes the oligomerizing N-terminal domains of DnaX (31) but preserves the glycine-rich region and residues 535-557, which are critical for ClpXP degradation.…”
Section: Partial Processing Of Dnax Requires Folded Domains Adjacent Tomentioning
confidence: 99%
“…The ubiquitin-proteasome system modulates Gli2 and Gli3 activity in two ways: it completely degrades the fully activated transcription factors in the presence of Hh and partially degrades Gli2 and Gli3 to convert them to repressors in the absence of Hh [116]. While the most common function of the proteasome is to degrade proteins completely, partial processing occurs when the proteasome runs into a folded domain that stalls its progress along the polypeptide, giving the remainder of the protein a chance to escape degradation.…”
Section: Partial Degradation Of Gli2 and Gli3mentioning
confidence: 99%
“…Transplanting the PDD of Gli3 into Gli2 was able to transfer the ability to be processed efficiently. However, it was later established that the PDD was not sufficient to induce partial proteasomal degradation of Gli1, and further studies revealed that the processing signal is encoded in three distinct regions of Gli3: the Zn-finger domain, a linker region, and a degron sequence [116].…”
Section: Partial Degradation Of Gli2 and Gli3mentioning
confidence: 99%
“…The increased efficiency of Gli3 processing is due in large part to the sequence of a 200-residue processing determinant domain in its C terminus (79). Together with an appropriate degron and the zinc finger domain, the processing determinant domain forms a three-part signal that is essential for efficient Gli3 processing (80). But what happens to Gli2-FL in the absence of Hh?…”
Section: Transcriptional Repression In Absence Of Hedgehogmentioning
confidence: 99%